Assessing Skill Needs for Community-Based Training in Rural Philippines - Ybañez, Romario; Diaz, Christian; Diaz, Shela (Journal of Interdisciplinary Perspectives, 2025)
Rural communities in the Philippines continue to face persistent challenges in accessing structured training programs that build essential administrative and digital skills. Despite the increasing demand for professional competence among grassroots stakeholders, many remain underserved by capacity-building initiatives that are not tailored to their specific contextual realities. This study was conducted to address the identified gap in community-based training opportunities for both local government officials and senior high school students in Barangay Masaplod Sur, Dauin, Negros Oriental. Guided by Maslow’s Hierarchy of Needs, Systems Theory, and Social Action Theory, the research employed a descriptive quantitative approach utilizing a researcher-developed survey instrument. Key areas explored included socio-demographic characteristics, perceived urgency for training, self-rated skill levels, and motivations for participation. Findings revealed that most respondents had little to no exposure to formal training programs, particularly in areas such as records management, office administration, and digital proficiency. The study also noted a mismatch between the community's training needs and the existing support mechanisms available to them. These insights underscore the critical role of higher education institutions in designing and delivering localized extension programs that bridge these capability gaps. By aligning training initiatives with the actual needs and motivations of rural stakeholders, the study advocates for inclusive development strategies that strengthen both governance and employability at the community level.